(3GdJLGhR hGdaQGZs - (3eMeO LeGd GdgGTej, cGf MjG (B1391 (3g`s ((3GdeDdas)
(3ChdgG (B:s
... .. (3hfMh GdMOjK MSH JaSjQ Ydj Hf EHQGgje Gdbej Yf GdEeGe GdHGbQ Cfg GdZfGA hTQH GdNeQ hSGFQ GdedGgj ceG jDjO Pdc eYGfj GdCNHGQ (B...s
(3BNQgG (B:s
... (3agh jTc aj GdhVhO HYOeG jaQZ efg hjYjQ aj MGd ZjQ MGd GdhVhA eG jUjQ aj GdUdGI Ch aj ZjQgG haj GdMGdI GdKGfjI jTc aj HYV eG ChLHg (B...(3aj GdYed HYO GdaQGZ efg (B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs